2009
DOI: 10.1590/s0034-70942009000400005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Of Preoperative Anxiety And Depression In Patients Undergoing Invasive Cardiac Procedures

Abstract: Patients with cardiac diseases undergoing electrophysiological studies, pacemaker implantation, and myocardial revascularization have different levels and prevalence of anxiety, but they do not show differences in the level and prevalence of depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 20 publications
1
12
1
10
Order By: Relevance
“…Two studies have previously found no relationship between anxiety and parameters such as gender, smoking status, marital status, and educational status. [219] However, our study found that anxiety decreased as the level of education increased. We also found that patients previously undergoing neuraxial anesthesia had less anxiety when compared to others.…”
Section: Discussioncontrasting
confidence: 59%
“…Two studies have previously found no relationship between anxiety and parameters such as gender, smoking status, marital status, and educational status. [219] However, our study found that anxiety decreased as the level of education increased. We also found that patients previously undergoing neuraxial anesthesia had less anxiety when compared to others.…”
Section: Discussioncontrasting
confidence: 59%
“…En el pre-operatorio de cirugía general, la presencia de ansiedad y depresión, medida por la Escala Hospitalaria de Ansiedad y Depresión (HADS) fue estimada en 44,3% y 26,6%, respectivamente (7) . En estudio del pre-operatorio de cirugía de revascularización miocárdica, la presencia de ansiedad y depresión investigada con la misma escala se presentó en 34,4% y 28,1%, respectivamente, reforzando la importancia del uso de esa escala en la detección precoz de esos síntomas (8) .…”
Section: Enfermería Globalunclassified
“…La Escala Hospitalaria de Ansiedad y Depresión (HADS) está compuesta por 14 cuestiones, siendo 7 para evaluar ansiedad y 7 para depresión, siendo cada ítem puntuado en una escala de 0 a 3, en un total de 21 puntos para cada escala. Será adoptado el punto de corte de: sin ansiedad o depresión de 0 a 8, con ansiedad o depresión > 9 en cada sub-escala, respectivamente (7,8) . Esa escala ha sido utilizada por su uso rápido y simple (en hasta diez minutos), por haber sido demostrada su validad y confiabilidad en varios estudios y por no contener evaluación de síntomas somáticos (8) .…”
Section: Métodounclassified
“…Anksiyete, kolonoskopi, gastroskopi, bronkoskopi, invaziv kardiyak girişimler, miyokard perfuzyon sintigrafisi ve manyetik rezonans görüntüleme (MRG) gibi birçok medikal ve cerrahi prosedür sirasinda sik görülebilen bir durumdur [1][2][3][4][5][6][7][8][9].…”
unclassified